An Analysis of Deixis in The Lyrics of A Song “Man Upon The Hill” by The Stars and Rabbit - Anggraeni, Mita Nur; Husnussalam, Hendra (IKIP Siliwangi, 2025)
The purpose of this study is to analyze the predominant deixis and the form of deixis found in the famous band Stars and Rabbit song